2018
DOI: 10.24953/turkjped.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Complications of cardiac catheterization in children with congenital heart disease

Abstract: Tokel K, Gümüş A, Ayabakan C, Varan B, Erdoğan İ. Complications of cardiac catheterization in children with congenital heart disease. Turk J Pediatr 2018; 60: 675-683.Catheterization procedures for congenital heart disease include a broad range of procedures with a large spectrum of potential adverse outcomes. We aimed to determine the incidence of various complications during pediatric cardiac catheterizations and to designate the relative risk factors for such complications.All pediatric patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
8
6
Order By: Relevance
“…We obtained a shorter time in terms of arterial access time compared to those of studies that used traditional technique and US-GFAA. 2,5,7,13,15,20 Although a study reported that long access time increases the complications of the access site, 13 our study did not identify arterial access time as a risk factor in patients with ALAP and PFAO.…”
Section: Discusioncontrasting
confidence: 72%
See 4 more Smart Citations
“…We obtained a shorter time in terms of arterial access time compared to those of studies that used traditional technique and US-GFAA. 2,5,7,13,15,20 Although a study reported that long access time increases the complications of the access site, 13 our study did not identify arterial access time as a risk factor in patients with ALAP and PFAO.…”
Section: Discusioncontrasting
confidence: 72%
“…7,19 Several studies have reported that prolonged cannulation time increases arterial occlusion and access site complications. 13,17,18 In our cohort , the cannulation time in was significantly shorter than in previous studies. 7,13,15 The cannulation time was statistically longer in patients with ALAP than in those without ALAP.…”
Section: Discusioncontrasting
confidence: 61%
See 3 more Smart Citations